CHH_vd: database of genes and variants associated with Congenital Hypogonadotropic Hypogonadism - Brunello, Franco Gino (2025)
We systematically collected variants reported in the scientific literature as causal for Congenital Hypogonadotropic Hypogonadism (CHH [MIM 146110]) and created CHH_vd, a well-annotated, curated database of variants. The identified sequence variants were critically evaluated using the American College of Medical Genetics and Genomics (ACMG)/ Association for Molecular Pathology (AMP) standards and related guidelines. For variant interpretation, we implemented a novel custom-built computational pipeline for variant annotation and classification.